2003
DOI: 10.1055/s-2003-37197
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Expression After Repeated Bouts of Eccentric Exercise

Abstract: Plasma interleukin-6 (IL-6) is known to increase in response to eccentric exercise due to an acute-phase immune response. However, the severity of muscle injury is reduced with repeated bouts of eccentric exercise, possibly as a result of decreases in plasma IL-6. This study determined the response of IL-6 mRNA and IL-6, troponin-I (sTnI), muscle strength, and soreness as a result of repeated bouts of eccentric exercise. Eight males underwent two eccentric exercise bouts (3 wk apart) involving 7 sets of 10 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 26 publications
7
63
1
6
Order By: Relevance
“…2), clearly demonstrating that muscle damage is not required to increase plasma IL-6 during exercise. Rather, eccentric exercise may result in a delayed peak and a slower decrease of plasma IL-6 during recovery (135,203,396).…”
Section: Exercise and Cytokines With Focus On Interleukin-6 A Symentioning
confidence: 99%
“…2), clearly demonstrating that muscle damage is not required to increase plasma IL-6 during exercise. Rather, eccentric exercise may result in a delayed peak and a slower decrease of plasma IL-6 during recovery (135,203,396).…”
Section: Exercise and Cytokines With Focus On Interleukin-6 A Symentioning
confidence: 99%
“…Moreover, it has become evident that eccentric exercise is not associated with a larger increase in plasma IL-6 than exercise involving concentric "nondamaging" muscle contractions, clearly demonstrating that muscle damage is not required to increase plasma IL-6 during exercise. Rather, eccentric exercise may result in a delayed peak and a slower decrease of plasma IL-6 during recovery [157][158][159].…”
Section: Acute Changes Of Systemic Inflammatory Markers During and Afmentioning
confidence: 99%
“…In resting human skeletal muscle, the IL-6 mRNA content is very low, while small amounts of IL-6 protein predominantly in type I fibers may be detected using sensitive immunohistochemical methods [171]. In response to exercise, an increase of the IL-6 mRNA content in the contracting skeletal muscle is detectable after 30 min of exercise, and up to 100-fold increases of the IL-6 mRNA content may be present at the end of the exercise bout [172,173]. Nevertheless this, although the earlier studies demonstrated that IL-6 mRNA is increased in skeletal muscle biopsy samples, they did not prove that skeletal muscle is the source of the increase in the contraction-induced increase in IL-6.…”
Section: Acute Changes Of Systemic Inflammatory Markers During and Afmentioning
confidence: 99%
“…165,179 Repeated bouts of eccentric exercise have been shown to increase intramuscular stores of heat shock proteins, which may be responsible for skeletal muscle-specific anti-inflammatory effects following a period of chronic resistance exercise training. 180,181 Acute bouts of eccentric exercise damage skeletal muscle, which results in a release of HSP60 and HSP70 into the circulation. 182,183 During repeated bouts of eccentric exercise, separated by 2 weeks, skeletal muscle inflammatory cytokine release decreases, 180,181 which is consistent with an anti-inflammatory adaptation.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…180,181 Acute bouts of eccentric exercise damage skeletal muscle, which results in a release of HSP60 and HSP70 into the circulation. 182,183 During repeated bouts of eccentric exercise, separated by 2 weeks, skeletal muscle inflammatory cytokine release decreases, 180,181 which is consistent with an anti-inflammatory adaptation. Heat shock proteins have been implicated as a possible crosstolerance signal, which influence blood monocyte/peripheral macrophage LPS-stimulated inflammatory cytokine production and hepatic acute phase protein production.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%